2008
DOI: 10.1038/gt.2008.179
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of intratumoral administration of recombinant oncolytic adenovirus overexpressing HSP70 in advanced solid tumor patients

Abstract: Our pre-clinical studies demonstrated that intratumoral vaccination with a recombinant oncolytic type 2 adenovirus overexpressing the heat shock protein (HSP)70 protein, designated as H103, can inhibit primary and metastatic tumors through enhanced oncolytic activity and HSPmediated immune responses against shared and mutated tumor antigens. In the pre-clinical studies of local H103 administration, no significant toxicity was observed in the animal trials with mice, cavy or rhesus monkeys. A phase I clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 29 publications
1
57
0
2
Order By: Relevance
“…Several clinical trials using oncolytic Ads have been carried out, and promising results have been reported (3)(4)(5). Various types of oncolytic Ads have been developed, and can be mainly classified into 2 groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials using oncolytic Ads have been carried out, and promising results have been reported (3)(4)(5). Various types of oncolytic Ads have been developed, and can be mainly classified into 2 groups.…”
Section: Introductionmentioning
confidence: 99%
“…55 Two follow-up products have been introduced, H102, currently in pre-clinical testing, and H103, an oncolytic type 2 adenovirus overexpressing the heat shock protein HSP 70 , recently tested as a intratumoral vaccination in a completed phase I clinical trial in patients with advanced solid tumors. 56 Transient and partial regression of distant, un-injected tumors was observed in three patients during this study, and because of promising clinical antitumor activity and positive safety outcome further studies are being pursued.…”
Section: Onyx 015mentioning
confidence: 83%
“…III фаза клинических испытаний препарата Oncorine™ была проведена в сочетании с химиотерапией препара-тами цисплатин и 5-фторурацил [56]. Больные получали интратуморальные инъекции препарата Oncorine™ еже-дневно в течение 5 дней, цикл введения повторяли каж-дые 3 недели.…”
Section: Oncorine™ (н-101) в 2005 г китайской регулирующей организацunclassified